Cho A (x) = 1 + 2x -x2
B (x) = x2+ 3 - 2x
Tinh A (x) + B (x)
B (x) - A (x)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bạn chú ý đăng lẻ câu hỏi! 1/
a/ \(=x^3-2x^5\)
b/\(=5x^2+5-x^3-x\)
c/ \(=x^3+3x^2-4x-2x^2-6x+8=x^3=x^2-10x+8\)
d/ \(=x^2-x^3+4x-2x+2x^2-8=3x^2-x^3+2x-8\)
e/ \(=x^4-x^2+2x^3-2x\)
f/ \(=\left(6x^2+x-2\right)\left(3-x\right)=17x^2+5x-6-6x^3\)
\(A=6x^2+23x+21-\left(6x^2+23x-55\right)=76\\ B=x^4+x^3-x^2-2x^2-2x+2-x^4-x^3+3x^2+2x\\ =2\\ C=x^4+x^3-3x^2-2x-\left(x^4+x^3-x^2-2x^2-2x+2\right)\\ =-2\)
a, \(A=2x^3-9x^5+3x^5-3x^2+7x^2-12=-6x^5+2x^3+4x^2-12\)
b, \(B=2x^4+x^2+2x-2x^3-2x^2+x^2-2x+1=2x^4-2x^3+1\)
c, \(C=2x^2+x-x^3-2x^2+x^3-x+3=3\)
1) A = \(\dfrac{2x-1}{x+3}\) = \(\dfrac{3}{2}\) (=) (2x-1).2 = 3.(x+3)
(=) 4x-2 =3x+9
(=) 4x-3x = 9+2
(=) x = 11 (tm)
2) Để \(\dfrac{A}{B}\)< \(^{x^2}\)+5 (=) \(\dfrac{2x-1}{x+3}\): \(\dfrac{2}{x^2-9}\) < \(x^2\)+5
(=) \(\dfrac{\left(2x-1\right)}{\left(x+3\right)}.\dfrac{\left(x-3\right)\left(x+3\right)}{2}\) < \(x^2\)+5
(=) \(\dfrac{\left(2x-1\right).\left(x-3\right)}{2}< x^2+5\)
(=) \(\dfrac{2x^2-6x-x+3}{2}\) < \(x^2\) +5
(=) \(2x^2\)- 7x + 3 < \(2x^2\)+ 10
(=) (\(2x^2\)-\(2x^2\)) - 7x < -3 +10
(=) -7x < 7
(=) x > -1
A(x) + B(x) = 1 + 2x - x2 + x2 + 3 - 2x
= ( 1 + 3 ) + ( x2 - x2 ) + ( 2x - 2x )
= 4 + 0 + 0
= 4
B(x) - A(x) = ( x2 + 3 - 2x ) - ( 1 + 2x - x2 )
= x2 + 3 - 2x - 1 - 2x + x2
= ( x2 + x2 ) + ( 3 - 1 ) - ( 2x - 2x )
= 2x2 + 2 - 2x + 2x
= 2x2 + 2 - 2(2x)
= 2x2 + 2 - 4x